2018
DOI: 10.3892/ol.2018.9777
|View full text |Cite
|
Sign up to set email alerts
|

miR‑7‑5p inhibits cell migration and invasion in glioblastoma through targeting SATB1

Abstract: MicroRNAs (miRNAs/miRs) have been revealed to influence the development and progression of glioblastoma. Although a number of miRNAs are abnormally expressed in glioblastoma it is not clear whether they are a factor associated with glioblastoma pathogenesis. In the present study, miR-7-5p was identified as being aberrantly downregulated in glioblastoma tissues and cell lines. miR-7-5p overexpression significantly decreased the migratory and invasive capacity of the cells, while miR-7-5p silencing had the oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Zhu et al demonstrated that miR-7-5p suppresses cell migration and invasion by targeting SOX18 in pancreatic ductal adenocarcinoma [26]. MiR-7-5p has been found to target and regulate the genes as SATB1 and PARP1 in some cancer diseases as we have mentioned before [27,28]. MiR-7-5p may have several target genes similar to miR-137; such target genes are critical oncogenic factors, including TGFβ2, that could further regulate brain tumorigenesis [29].…”
Section: Discussionmentioning
confidence: 88%
“…Zhu et al demonstrated that miR-7-5p suppresses cell migration and invasion by targeting SOX18 in pancreatic ductal adenocarcinoma [26]. MiR-7-5p has been found to target and regulate the genes as SATB1 and PARP1 in some cancer diseases as we have mentioned before [27,28]. MiR-7-5p may have several target genes similar to miR-137; such target genes are critical oncogenic factors, including TGFβ2, that could further regulate brain tumorigenesis [29].…”
Section: Discussionmentioning
confidence: 88%
“…miR-214-3p plays an important role in depressive-like behaviours, cognition defects, Alzheimer's disease, and endothelial cell dysfunction and mediates neural apoptosis, neuropathic pain, and the growth, migration, and invasion of glioma cells [60][61][62][63][64][65]. miR-7-5p is relevant to vascular endothelial cell proliferation, glioma, brain damage, and cognitive dysfunction [66][67][68][69]. Moreover, it has been reported that miR-7-5p boosts apoptosis but inhibits cell proliferation and apoptosis of T lymphocytes, explaining the function of miR-214-3p and miR-7-5p in psoriasis [70,71].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%
“…This type of regulation may lead to a novel manner of inhibiting the expression of pathogenic genes that could potentially be used in small RNA drug development. MIR-7 was first discovered as a tumor suppressor, which achieved anti-tumor effects by directly targeting tumor growth-promoting genes or modifying regulatory tumor suppressor factors [49][50][51][52][53][54]. In addition to anti-tumor effects, miR-7 also undergoes expression changes after viral infection and plays a role in antiviral defense by regulating gene expression and related pathways in host cells.…”
Section: Discussionmentioning
confidence: 99%